Psychological aspects of infertility - results from an actor-partner interdependence analysis = Psychische Aspekte bei unerfülltem Kinderwunsch - Ergebnisse einer Akteur-Partner-Interdependenz-Analyse - Thanscheidt, Carla; Pätsch, Patrick; Rösner, Sabine; Germeyer, Ariane; Krause, Manja; Kentenich, Heribert; Siercks, Ikbale; Häberlin, Felix; Ehrbar, Verena; Tschudin, Sibil; Böttcher, Bettina; Toth, Bettina; et al. (Geburtshilfe und Frauenheilkunde, 2023)
Introduction: For some patients, undergoing medical treatment for infertility is a cause of major emotional stress which the couple needs to deal with together; it can be said that infertility is a shared stressor. From the literature it is known that a subjectively perceived sense of self-efficacy supports the patient’s ability to cope adaptively with an illness. As the basis for this study, we assumed that high levels of self-efficacy are associated with low psychological risk scores (e.g., for anxiety or depressiveness), both in the patient themselves and in their partner. Accordingly, in infertility patients, targeted support to promote helpful self-efficacy expectations could represent a new counselling strategy that could enable psychologically vulnerable patients to better cope with the treatment procedure and treatment failures of medically assisted reproduction, making these patients less at risk with regard to psychosocial factors. Methods: 721 women and men attending five fertility centers in Germany (Heidelberg, Berlin), Austria (Innsbruck), and Switzerland (St. Gallen, Basel) completed the SCREENIVF-R questionnaire to identify psychological risk factors for amplified emotional problems, as well as the ISE scale to measure self-efficacy. Using paired t-tests and the actor–partner interdependence model, we analyzed the data of 320 couples. Results: Considering the study participants as couples, women had a higher risk score than men for four out of five risk factors (depressiveness, anxiety, lack of acceptance, helplessness). In all of the risk areas, it was possible to identify a protective effect from self-efficacy on the patient’s own risk factors (actor effect). There was a negative correlation between the men’s self-efficacy level and the women’s feelings of depressiveness and helplessness (partner effect, man → woman). The women’s self-efficacy levels had a positive correlation with acceptance and access to social support in the men (partner effect, woman → man). Conclusion: Because infertility is generally something that a couple has to deal with together, future studies should focus on couples as the unit of analysis instead of just analyzing the men and women separately. In addition, couples therapy should be the gold standard in psychotherapy for infertility patients.
Artikel online veröffentlicht: 14. April 2023
Gesehen am 28.08.2023